Kader Promosi Kesehatan Preventif Penyalahgunaan Napza - Nurul Kurniati; Dhesi Ari Astuti (Jurnal Surya Masyarakat, 2020)
Drug users in DIY from 2008 to 2015 have increased. Data from the State Narcotics Agency said that drug users in 2008 were 2.72%, in 2011 2.8% and 2015 were 3.37%. The purpose of this activity is to form a cadre of preventive health promotion for adolescents. The method of implementing the activity is by forming cadres who have been trained and conducting socialization to other teenagers to motivate drug tests. The result was formed 15 cadres or observers and socialized prevention efforts of 46 drug users who were motivated by drug testing. The output of this activity is in addition to the formation of cadres and adolescents who are socialized can increase public knowledge related to the dangers of drug abuse.